2011
DOI: 10.1111/j.1440-1789.2010.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autophagy in temozolomide treated malignant gliomas

Abstract: Autophagy is a dynamic process of protein degradation. Induction of autophagy by temozolomide (TMZ) has been noted in glioma cell lines. Twenty-eight specimens, obtained from 14 patients before and after TMZ treatment, were analyzed to investigate whether induction of autophagy could be detected in surgical specimens by immunohistochemical analysis. Macroautophagy was monitored by immunohistochemical analysis employing anti-light chain 3 isoform B (LC3B) and anti-lysosome-associated membrane protein 1 (LAMP1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens (11,12). In agreement with this, the current results showed that treatment with 100 µM TMZ induced autophagy as shown by a significant increase of AVOs and enhanced cleavage of LC3B (Fig.…”
Section: Tmz Treatment Induces Autophagy In Gliomasupporting
confidence: 78%
See 1 more Smart Citation
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens (11,12). In agreement with this, the current results showed that treatment with 100 µM TMZ induced autophagy as shown by a significant increase of AVOs and enhanced cleavage of LC3B (Fig.…”
Section: Tmz Treatment Induces Autophagy In Gliomasupporting
confidence: 78%
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens, and inhibition of autophagy augments TMZ-induced apoptosis in glioma cells (11,12). However, the molecular mechanism by which TMZ induces autophagy is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, autophagy induces the death of damaged cells, and yet at other times, autophagy confers protection [47] . Indeed, autophagy induction functions as a pro-death mechanism (also called type II programmed cell death) in different tumors [48][49][50] . Treatment with NVP-BEZ235 increased autophagy, as measured by studying LC3-I to LC3-II conversion over an extended period of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, autophagic cell death could also be initiated in response to sustained intracellular damage caused by hypoxia, chemotherapeutic agents, virus infection, or toxins, especially in gliomas (17). Recent studies found that GBM is resistant to chemotherapy protocols that induce apoptosis but seems to be less resistant to therapies that induce autophagy (18)(19)(20). As an effective cytotoxic drug, temozolomide (TMZ) induces significant autophagic cell death in many GBM cells, such as U251 human glioma cell line (18,21,22).…”
Section: Introductionmentioning
confidence: 99%